Alternative education for undocumented children: An input evaluation - Wirawati Ngui Yi Xe; Vincent Pang; Chiam Sun May; Rose Patsy Tibok; Crispina Gregory K Han (Penerbit Akademi Baru, 2023)
This study evaluated an alternative learning centre which caters to undocumented children in the state of Sabah, Malaysia. The model for evaluation was derived from Stufflebeam’s Context Input Process Product (CIPP) model. To evaluate the input of the centre, semi-structured interviews were conducted with relevant stakeholders. The sample included the head of the village, members of the village security development committee, the teachers of the centre, and an officer from the government body responsible for the centre’s management. The study collected data related to the strategies and activities (vision and mission, curriculum) and the resources (teaching staff, community support, financial resources, materials, and facilities) of the centre. The study revealed that the centre’s primary goal is to provide undocumented children with basic education; however the curriculum was brief, loosely prescribed, with no standardised assessment. Important resources were basic if not limited, and this accordingly restricted the centre from realising its full potential as an education hub. Based on the findings of this study, recommendations to assist future planning and improve the centre were put forward.